Effectiveness of neuraminidase inhibitors to prevent mortality in patients with laboratory-confirmed avian influenza A H7N9. (February 2021) - Cheng, Wei; Pan, Anqi; Rathbun, Stephen L.; Ge, Yang; Xiao, Qian; Martinez, Leonardo; Ling, Feng; Liu, Shelan; Wang, Xiaoxiao; Yu, Zhao; Ebell, Mark H.; Li, Changwei; et al.
Highlights: Evidence-based research on the effectiveness of neuraminidase inhibitors for H7N9 infection was lacking. Several observational studies have reached inconsistent conclusions. Analyses were performed on all laboratory-confirmed cases in Zhejiang Province between 2013 and 2017. Time-dependent survival models and multiple imputation on missing data were used. No association was found between treatment with neuraminidase inhibitors and survival in patients with H7N9 infection. Abstract: Objectives: Avian influenza virus A(H7N9) remains a threat to humans and has great potential to cause a pandemic in the foreseeable future. Antiviral treatment with neuraminidase inhibitors has been recommended to treat patients with H7N9 infection as early as possible, although evidence-based research on their effectiveness for H7N9 infection is lacking. Methods: Data from all laboratory-confirmed cases of H7N9 infection in Zhejiang Province between 2013 and 2017 were retrieved, and time-dependent survival models were used to evaluate the effectiveness of treatment with neuraminidase inhibitors to reduce the risk of mortality. Results: The final optimal model found no significant association (odds ratio 1.29, 95% confidence interval 0.78–2.15) between time to treatment with neuraminidase inhibitors and survival after controlling for age and white blood cell count. Sensitivity analyses with multiple imputation for missing data concurred with the primary analysis. Conclusions: No association was found between treatment with neuraminidase inhibitors and survival in patients with H7N9 infection using various adjusted models and sensitivity analyses of missing data imputations.